Abomasal disorders in cattle: Insights into prevalence, clinico-pathology and ultrasonographic examination - M, SARAVANAN; P, HEMALATHA; N, PREMALATHA; K, JAYAKUMAR; P, SUMITHA; K, KARTHIKA (The Indian Journal of Animal Sciences, 2025)
This study was carried out to study the prevalence and comprehensive approaches in the diagnosis of abomasal disorders in cattle. The prevalence of abomasal disorders was 41.7% of abomasal ulcer, 33.3% of right displacement of abomasum, 16.7% of left displacement of abomasum, 5.6% of abomasal bloat and 2.8% of abomasal impaction. Crossbreed Jersey cow and recently calved animals were predominantly affected. Absence of feed intake, decreased milk yield, absence of rumination, bruxism and fed with rice were recorded as common history of abomasal disorders. Predominant clinical findings of animals affected with abomasal disorders were depressed demeanour, bruxism, pale conjunctiva, reduced rumen protozoa, melena and tachycardia. Nine cases were positive for fecal occult blood test and 10 cases of melena were noticed. Reduction in Hb, PCV, RBC, MCHC, TP and globulin were observed in the abomasal disorder cases. Increased BUN and bicarbonate level were noticed. Reduction in serum calcium, phosphorous and potassium were noticed. Rumen chloride was increased in all the abomasal disorder cases. Highly significant increases in the serum pepsinogen and NEFA were noticed in all the abomasal disorders. The ultrasonographic changes were assessed in all abomasal disorders based on location, echogenicity of abomasal contents and motility. Staphylococcus thermophiles, Bacillus thermophiles, Candida spp., Pseudomonas spp. and Fusobacterium spp. were isolated from abomasal fluid. Comprehensive approach enables early detection and timely implementation of treatment and management protocols for abomasal disorders in cattle.